Generalized Landau Yang theorem - T. R. Govindarajan; Rakesh Tibrewala (Journal of High Energy Physics)
Abstract Landau Yang theorem is well known for the past several decades. It prohibits the decay of a massive spin 1 particle to two photons. This emerges simply from the representation theory of the Poincare group and Bose Statistics. It does not require any action or Lagrangian. We generalize this theorem to theories with supersymmetry (SUSY) which disallows even decay to two photinos (Majorana fermions) as well as the decay of a zino to a photon and a photino. We will prove that if the photon has a mass, howsoever small, this theorem can be evaded. We also show that the supersymmetric selection rule above can also be evaded through the Stueckelberg mass term. Further interesting implications are also pointed out.